2001
DOI: 10.1161/hc3101.093906
|View full text |Cite
|
Sign up to set email alerts
|

Shock Reduction Using Antitachycardia Pacing for Spontaneous Rapid Ventricular Tachycardia in Patients With Coronary Artery Disease

Abstract: Background-Implantable cardioverter-defibrillators (ICDs) can terminate some ventricular tachycardias (VTs) painlessly with antitachycardia pacing (ATP). ATP has not routinely been applied for VT Ͼ188 bpm because of concerns about efficacy, risk of acceleration, and delay of definitive shock therapy. This prospective, multicenter study evaluated the efficacy of empirical ATP to terminate fast VT (FVT; Ͼ188 bpm). Methods and Results-Two hundred twenty coronary artery disease patients received ICDs for standard … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
226
0
10

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 302 publications
(244 citation statements)
references
References 22 publications
6
226
0
10
Order By: Relevance
“…This programming might improve survival [126]. Indeed, several studies have shown that ATP is effective at terminating slow and fast VT with exceedingly low rates of adverse events like syncope [93,135,[161][162][163][164][165]. The initial bias of the ICD community was to reserve ATP therapy for those patients in whom the therapy was demonstrated to be effective, usually during an electrophysiologic study.…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
See 1 more Smart Citation
“…This programming might improve survival [126]. Indeed, several studies have shown that ATP is effective at terminating slow and fast VT with exceedingly low rates of adverse events like syncope [93,135,[161][162][163][164][165]. The initial bias of the ICD community was to reserve ATP therapy for those patients in whom the therapy was demonstrated to be effective, usually during an electrophysiologic study.…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
“…It is not reflective of the arrhythmias experienced outside the electrophysiology laboratory for primary and secondary prevention patients with ischemic and nonischemic substrates [101,166]. Although the ideal number of ATP bursts has not been definitively determined, current data support the use of up to 2 ATP attempts, given additional attempts yield very little additional efficacy [93,135,[161][162][163][164][165]167,168]. In one study, up to 5 attempts were found to be safe [168].…”
Section: Tachycardia Therapy Programmingmentioning
confidence: 99%
“…ATP was equally effective in patients without coronary artery disease, a group excluded from the pilot study, PainFREE Rx. 11 The greatest predictor of ATP success in PainFREE Rx was NSVT. 11 One may infer that the device was claiming ATP success for treating nonsustained FVT episodes that were destined to terminate regardless of therapy, a reasonable conclusion given that VF plus FVT detection used 12 of 16 intervals.…”
Section: Discussionmentioning
confidence: 98%
“…11 The greatest predictor of ATP success in PainFREE Rx was NSVT. 11 One may infer that the device was claiming ATP success for treating nonsustained FVT episodes that were destined to terminate regardless of therapy, a reasonable conclusion given that VF plus FVT detection used 12 of 16 intervals. Consequently, this trial used 18 of 24 intervals for VF plus FVT detection and found that NSVT was not a predictor of ATP success.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation